Seasonal and annual rainfall variability over East Hararghe Zone, Oromia, Ethiopia - Asalfew Negussie Cheru; Tesfaye Dessu Geleta; Gezahegn Mergia Tullu (Academia Environmental Sciences and Sustainability)
Rainfall is one of the most important climate elements for agricultural production throughout the world. This study analyzes the seasonal and annual rainfall variability and its implications on agriculture production in the East Hararghe Zone of Oromia, Ethiopia. Rainfall is a critical factor influencing agricultural productivity and water resource management in this region, where agriculture serves as the mainstay of the economy and livelihood for millions. Utilizing historical precipitation data from meteorological stations across East Hararghe from 1981 to 2023, we employed statistical methods to analyze trends, patterns, and anomalies in both seasonal (Kiremt and Belg) and annual rainfall totals. This study used GeoCLIM version 1.2.1, ArcGIS version 10.3.1, and QGIS 3.12.1, and Python version for data analysis. The findings revealed that significant seasonal and inter-annual variability characterized by periods of extreme weather events that have profound implications for food security. There are two main rainy seasons, the Belg (February, March, April, and May; short rains) and the Kiremt (June, July, August, and September; long rains), and one dry season, the Bega (October, November, December, and January; no rain). The Kiremt season (June to September), essential for crop cultivation, exhibits distinct fluctuations linked to regional climate phenomena such as El Niño/La Niña–Southern Oscillation. Moreover, our results indicated an increasing trend of Kiremt rainfall standardized anomaly during 2007, 2014, 2019, and 2020 but also highlighted concerning patterns of erratic distribution within the Belg season. Based on the results, we underscore the necessity for adaptive agricultural practices to mitigate risks associated with climate variability. Understanding these dynamics is vital for concerned sectors, policymakers, and researchers aiming to enhance resilience among vulnerable communities dependent on rain-fed agriculture.